2013
DOI: 10.1089/acm.2011.0681
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Antimicrobial Activity Associated with Ionic Colloidal Silver

Abstract: The study data support ionic colloidal silver as a broad-spectrum antimicrobial agent against aerobic and anaerobic bacteria, while having a more limited and specific spectrum of activity against fungi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 21 publications
0
17
0
2
Order By: Relevance
“…Antibiotics can have adverse effects on intestinal health by eliminating normal intestinal microbes (Antonopoulos et al, 2009). Silver is known to have antimicrobial properties (McQuillan et al, 2012; Morrill et al, 2013). It is unknown whether concurrent AgNP ingestion will enhance antimicrobial effects of a typically well-tolerated antibiotic dose, causing potential adverse effects due to disruption of normal gastrointestinal microbes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotics can have adverse effects on intestinal health by eliminating normal intestinal microbes (Antonopoulos et al, 2009). Silver is known to have antimicrobial properties (McQuillan et al, 2012; Morrill et al, 2013). It is unknown whether concurrent AgNP ingestion will enhance antimicrobial effects of a typically well-tolerated antibiotic dose, causing potential adverse effects due to disruption of normal gastrointestinal microbes (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, no viral growth was seen with any strains tested. 300 A recent study also showed that T lymphocyte (T)-tropic and macrophage (M)-tropic strains of HIV-1 were extremely susceptible to the AgNPs coated with polyurethane condom. 15 In a recent study, different types of nanosilver particles were biosynthesized from F. oxysporum (4-13 nm), Curvularia spp.…”
mentioning
confidence: 99%
“…Гамалеи, была доказана анти-микробная активность in vitro протеината серебра в виде 2%-ного водного раствора в отношении основных бакте-риальных возбудителей заболеваний верхних дыхатель-ных путей: Staphylococcus spp. [20].…”
unclassified